2017
DOI: 10.1371/journal.pone.0184793
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-based selective autophagy-induction rescues ΔF508-CFTR and inhibits Pseudomonas aeruginosa infection in cystic fibrosis

Abstract: BackgroundCystic Fibrosis (CF) is a genetic disorder caused by mutation(s) in the CF-transmembrane conductance regulator (Cftr) gene. The most common mutation, ΔF508, leads to accumulation of defective-CFTR protein in aggresome-bodies. Additionally, Pseudomonas aeruginosa (Pa), a common CF pathogen, exacerbates obstructive CF lung pathology. In the present study, we aimed to develop and test a novel strategy to improve the bioavailability and potentially achieve targeted drug delivery of cysteamine, a potent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…pathways at the bench and bedside (58,(62)(63)(64)(65)(66)(67)(68)(69). Our data reveal that disrupting the delivery of CFTR disease-associated variants to both the UPS, via silencing of BAG1, and autophagosome, via the silencing of BAG3, corrects the trafficking defect associated with F508del-CFTR, leading to restoration of cellsurface activity.…”
Section: Bag3 Silencing Corrects F508del-cftrmentioning
confidence: 73%
See 1 more Smart Citation
“…pathways at the bench and bedside (58,(62)(63)(64)(65)(66)(67)(68)(69). Our data reveal that disrupting the delivery of CFTR disease-associated variants to both the UPS, via silencing of BAG1, and autophagosome, via the silencing of BAG3, corrects the trafficking defect associated with F508del-CFTR, leading to restoration of cellsurface activity.…”
Section: Bag3 Silencing Corrects F508del-cftrmentioning
confidence: 73%
“…Previously published efforts have emphasized the importance of autophagy in rescue of CFTR (58,(62)(63)(64)(65)(66)(67)(68)(69). Given the central role of BAG3 in the management of autophagy pathways for multiple targets (70 -74), we have demonstrated that reducing the cellular expression level of BAG3 generates a proteostatic environment that provides both chaperoning activity of F508del-CFTR, leading to improved biogenesis, and restoration of cell surface chloride channel activity.…”
Section: Discussionmentioning
confidence: 83%
“…The cysteamine drug (Lynovex ® , Novabiotics), an oral mucoactive, antibiofilm, and antibacterial agent, has passed the phase IIb clinical trial (NCT03000348) for use in the treatment of acute, infectious CF exacerbations [213]. PAMAM dendrimers were modified as cysteamine-like structure dendrimers (PAMAM-DEN CYS ), to obtain the antibiofilm activity of cysteamine [214]. PAMAM-DEN CYS demonstrated enhanced penetration across the thick mucus layer, thus, reducing biofilm formation, and the infection associated with P. aeruginosa [214].…”
Section: Nanocarriers For Cf Treatmentmentioning
confidence: 99%
“…Lumacaftor/ivacaftor for CF is a drug combination representative of restorative drugs. The majority of CF is caused by the deletion of F508 (ΔF508) in both alleles of the CFTR gene (Brockman et al 2017;Esposito et al 2016;Faure et al 2016). The ΔF508 CFTR proteins cannot be folded properly in ER lumen and are mostly degraded after failing to be exported to the cell membrane to perform its ion channel function (Fraser-Pitt and O'Neil 2015).…”
Section: Drug Efficacy and Toxicity: Restorative Drugmentioning
confidence: 99%